Pengaruh Kebijakan Subsidi BBM terhadap Ekspektasi Inflasi: Studi Empiris Perbandingan Antara Rumah Tangga dan Pedagang - Erdiana Br Manik; Febriana Krisdayanti Barus; Gustina Natalia Togatorop; Tria Indah Syahrani Lubis (GLOBAL SCIENTS PUBLISHER, 2026)
The fuel subsidy policy in Indonesia is used as a cushion against global energy price volatility; however, its price adjustments frequently trigger a surge in inflation expectations. This study was conducted to analyze the effect of the fuel subsidy policy on inflation expectations and to compare the differences in responses between households and traders. A comparative empirical study was carried out by analyzing data from 800 respondents (400 households and 400 traders) in the pre-policy period (August 2022) and the post-policy period (September 2022), when the price of Pertalite was raised by 31%. The analysis was performed using difference tests (t-test, Mann-Whitney U) and a Generalized Linear Model (GENLIN). The results showed that the fuel price increase significantly raised the inflation expectations of the entire sample (+5.76 percentage points, p<0.001). Response heterogeneity was observed: traders’ expectations jumped by +8.26 pp, whereas those of households rose by only +3.25 pp (Period×Group interaction: B=+5.009; p<0.001). The share of energy expenditure was identified as the only significant covariate (B=+0.042; p<0.001), while economic literacy and information access were found to have no effect. It is concluded that the fuel price hike policy has a greater impact on traders’ expectations than on those of households; therefore, segmented policy communication strategies are required. This study contributes to the literature on the heterogeneity of inflation expectations in developing countries and provides implications for Bank Indonesia in managing the expectations channel.